Enhancing ions/electrons dual transport in rGO/PEDOT:PSS fiber for high-performance supercapacitor. (15th April 2022) - Teng, Weili; Zhou, Qinqin; Wang, Xuekai; Gao, Junyan; Hu, Peng; Du, Yucheng; Li, Hongyi; Wang, Jinshu
Abstract: Enhancing the specific capacitance and rate performance of graphene based fiber-shaped supercapacitors (FSSCs) is critical to achieving advanced energy storage devices with desired performance. Here, hierarchically porous reduced graphene oxide/poly (3, 4-ethylenedioxythiophene):poly (4-styrenesulfonate) (rGO/PEDOT:PSS) hybrid fiber was constructed by co-assembling confined growth and acid treatment strategy. The rationally designed hybrid fiber addressed the issues of excellent conductivity and abundant porous channels for fast electrons transfer and rapid ions diffusion. As indicated, highly-oxidized small-sized GO precursor was utilized to endow rGO fiber with abundant ions diffusion channels and ions adsorption interfaces for double-layer capacitance, as well as ample oxygen functional groups for additional pseudocapacitance. The incorporation of acid-treated PEDOT:PSS also prevents the stacking of rGO sheets, improves the electrical conductivity and provides partial capacitance. Attributed to the synergy, the obtained hybrid fiber exhibits remarkably improved performance in FSSC with volumetric/areal specific capacitance of 226.5 F cm −3 /279.3 mF cm −2 at 0.5 A cm −3 and rate performance of 74.7% capacitance retention at 50 A cm −3, which is much superior to the counterpart of previously-reported FSSC devices. Meanwhile, the resultant FSSC device also exhibits superb electrochemical stability (91%, 10000 cycles), holding a great application prospect in wearable electronics. Graphical abstract: Image 1 Highlights: Highly-oxidized small-sized GO firstly used for rGO fiber to enhance ion diffusion. Highly-conductive acid-treated PEDOT:PSS spacer can facilitate electron transfer. The fiber in device shows high capacitance of 226.5 F cm −3 and rate performance. The fiber shaped supercapacitor shows superior energy density and cycle stability.